POTENSI LONGSOR AKIBAT AKTIVITAS PENAMBANGAN ILEGAL DI KECAMATAN SUNGAI DURIAN, KABUPATEN KOTABARU - Wahyuzi, Radhi; Muslim, Dicky; Zakaria, Zulfiadi; Sukiyah, Emi; Sophian, Raden Irvan (Jurnal Teknologi Mineral dan Batubara, 2024)
Generally, landslide potential can occur when a materials drifting force dominates the resisting force. A state of equilibrium is reached when the two aspects are in comparable conditions, or when the force of drift is less than the force of resistance. Spatial changes, morphological changes and changes in land use are often the cause of landslides if these changes are not properly planned and carried out without taking into account the principles of geotechnical engineering. One of the changes brought about by land use change is mining activity, in which very large morphological changes occur during the mining operation. These changes will usually have the potential to cause landslides if they are not managed in a proper and correct procedure. However, ilegal mining communities always appear and carry out mining operations without considering the principles of Good Mining Practices, so it will be quite dangerous for the environment and human beings, both in terms of potential landslide hazards and environmental damage. The purpose of this study is to determine the area and potential landslide hazard in the unlicensed community mining area using satellite imagery and slope stability analysis at the mining site. This research was conducted using a combination of geotechnical laboratory testing methods and field observations, as well as slope stability analysis, in order to determine the landslide potential at the research site. In general, the research data clearly shows that the slope formed due to ilegal mining activities has a factor of safety value in an unstable condition (0.516-1.076) with a probability of failure ranging from 15%-20%, and has a high consequence of failure status. The research data indicates that the research site is experiencing an unstable condition, which is likely the result of ilegal mining activities with the potential of landslides in the research site.